Optimization of aquaporin loading for performance enhancement of aquaporin-based biomimetic thin-film composite membranes - Zhao, Yang (2022)
The aquaporin-based biomimetic thin-film composite membrane (ABM-TFC) has demonstrated superior separation performance and achieved successful commercialization. The larger-scale production of the ABM membrane requires an appropriate balance between the performance and manufacturing cost. This study has systematically investigated the effects of proteoliposome concentration, protein-to-lipid ratio, as well as the additive on the separation performance of ABM for the purpose of finding the optimal preparation conditions for the ABM from the perspective of industrial production. Although increasing the proteoliposome concentration or protein-to-lipid ratio within a certain range could significantly enhance the water permeability of ABMs by increasing the loading of aquaporins in the selective layer, the enhancement effect was marginal or even compromised beyond an optimal point. Alternatively, adding cholesterol in the proteoliposome could further enhance the water flux of the ABM membrane, with minor effects on the salt rejection. The optimized ABM not only achieved a nearly doubled water flux with unchanged salt rejection compared to the control, but also demonstrated satisfactory filtration stability within a wide range of operation temperatures. This study provides a practical strategy for the optimization of ABM-TFC membranes to fit within the scheme of industrial-scale production.